Measuring women's experience of induction of labor using prostaglandin vaginal gel. (March 2017) - Beckmann, Michael; Thompson, Rachel; Miller, Yvette; Prosser, Samantha J.; Flenady, Vicki; Kumar, Sailesh
Abstract: Objective: To describe and examine the EXIT (EXperiences of Induction Tool), and report on the experience of women undergoing PGE2 vaginal gel IOL, who were participants in a randomized controlled trial comparing early amniotomy with repeat-PGE2. Study design: Following an evening dose of PGE2 vaginal gel, 245 women with live singleton term pregnancies were randomized to amniotomy or repeat-PGE2. Women's experience of IOL was a secondary outcome measure, assessed using the self-report EXIT administered by phone at 7–9 days post-partum. The 10-item EXIT assessed women's experiences in multiple domains using a 5-point agreement scale. Principal components analysis with orthogonal varimax rotation was undertaken to examine the scale structure. Internal consistency, face, content, construct and discriminant validity were also assessed. Results: The final 3-component solution comprised 8 of the 10 EXIT items, explained 76.1% of the variance and had a good fit to model (p < 0.001). The three resulting components were representative of women's experience of the time taken to give birth, discomfort with IOL, and subsequent contractions. The items loading to each component showed good internal consistency for time taken to give birth (α = 0.88), discomfort with IOL (α = 0.78), and experience of subsequent contractions (α = 0.87). Women in the repeat-PGE2 group reported a less favorable experience with the time taken to give birth (mean (SD): 3.5 (1.4) vs 3.9 (1.2); p = 0.04) and more discomfort with IOL (2.9 (1.1) vs 2.5 (1.0); p = 0.04) compared to women in the amniotomy group. At the individual item level, women in the amniotomy group responded more positive about the time taken to have their baby (median (IQR): 4 (3–5) vs 3 (2–5); p < 0.01); and less negative to the question about the number of vaginal examinations (2 (1–3) vs 2 (1–4); p = 0.05). Conclusions: The EXIT shows promise as an instrument for assessing women's experience of IOL. Women undergoing PGE2 vaginal gel IOL reports a more positive experience with an early amniotomy rather than with repeat-PGE2.